THE CONCEPT OF “PUBLIC POLICY” UNDER “BRUSSELS I” REGULATION - Kisieliauskaitė, Agnė (Teisė, 2017)
The article focuses on the concept of public policy, enshrined in „Brussels I“ regulation, and on a possibility to employ successfully this particular defence against free movement of judgements within the European Union.